Cervical cancer screening service utilization and associated factors among HIV positive women attending adult ART clinic in public health facilities, Hawassa town, Ethiopia: a cross-sectional study - Abiyu Ayalew Assefa; Feleke Hailemichael Astawesegn; Bethlehem Eshetu (BMC, 2019)
Abstract Background In Ethiopia, cervical cancer is a public health concern, as it is the second most cause of cancer deaths among reproductive age women and it affects the country's most vulnerable groups like; rural, poor, and HIV-positive women. Despite the strong evidence that cervical cancer screening results in decreased mortality from this disease, its utilization remains low. Methods An institution-based cross-sectional study was conducted from March 2 to April 1/2019 to assess the level and factors affecting utilization of cervical cancer screening among HIV positive women in Hawassa town. Quantitative data collection methods were used. Data were gathered using a structured and pretested questionnaire. Epi-Info version 7 and SPSS version 23 were used for data entry and analysis respectively. Statistically significant association of variables was determined based on Adjusted Odds ratio with its 95% confidence interval and p-value of ≤0.05. Results Of the 342 women interviewed, 40.1% (95% CI: 35.00, 45.33%) of them were screened. Having a post primary education (AOR = 5.1, 95% CI: 1.8, 14.5), less than 500 cell/mm3 CD4 count (AOR = 2.7, 95% CI: 1.2, 5.9); duration since HIV diagnosis (AOR = 4.2, 95% CI: 2.1, 8.5), partner support (AOR = 4.7, 95% CI: 2.3, 9.4), having knowledge about risk factors (AOR = 2.9 (95% CI: 1.2, 6.9) and having favorable attitude towards cervical cancer and its screening (AOR = 3.7 (95% CI: 1.8, 7.5) were associated with cervical cancer screening utilization. Conclusions The study revealed utilization of cervical cancer screening service was low among HIV positive women. Educational status, duration of HIV diagnosis, partner support, knowledge status about risk factor, CD4 count and attitude towards cervical cancer and its screening were associated with cervical cancer screening utilization. Health care workers need to provide intensive counseling services for all ART care attendants to increase utilization.